Comfort of earplugs: results of a field survey based on the COPROD questionnaire. Issue 9 (2nd September 2022) - Terroir, Jonathan; Perrin, Nellie; Wild, Pascal
Abstract: Many workers are exposed to noise levels that can cause hearing problems. Earplugs remain a common form of protection for workers exposed to hazardous levels. Their comfort directly affects the effective protection by influencing their consistent and correct use. In order to assess comfort, the COPROD questionnaire was previously developed on the basis of four comfort dimensions: acoustic, physical, functional and psychological. During this field survey, nine earplug models were evaluated by 118 participants over a 6-week period. This paper presents analyses of the collected data and compares three families of earplugs: roll-down foam, premolded and custom moulded. Analyses have shown a better rating of custom moulded earplugs in terms of overall comfort and for all dimensions of comfort. Although premolded earplugs are generally preferred to roll-down foam earplugs, from a statistical point of view, the evaluations of these two families are not significantly different for numerous characteristics. Practitioner Summary: Earplugs comfort conditions the hearing protection of the users. The COPROD questionnaire was developed to jointly evaluate all dimensions of comfort. Nine earplugs models were evaluated by 118 participants during 6 weeks. This paper presents analyses of the collected data.